The relationship between university readiness and academic achievement in a sample of among undergraduate students - Mohammad Sofian, Mohammad Luqman Syafii; Abdul Rahman, Shukran (2018)
The purpose of this research is to examine the level of university readiness among undergraduate university students in Malaysian Higher Learning Institutions (HLI); and to study the relationship between university readiness and academic achievement among undergraduate students in Malaysian Higher Learning Institutions. Data were gathered through responses to the University Readiness Scale, from the sample participants of undergraduate students of a Higher Learning Institution (HLI). The findings supported the research questions addressed in line with the research objectives. The average level of University Readiness of undergraduate students in the HLI is 77%, M=354 (SD=34.55). From the results, it was found that University Readiness predicts academic achievement of the undergraduate students in Malaysian HLI. The results of the study is expected to help HLIs to design appropriate interventions that could prepare students to be highly ready for university education, which in turn leads them to attain better academic achievement. A readier student will be able to acquire more competencies throughout their undergraduate program and will be able to compete healthily in the job market.